Large-Eddy Simulation of a Turbulent Spray Flame Using the Flamelet Generated Manifold Approach. (December 2015) - Andreini, A.; Bertini, D.; Facchini, B.; Puggelli, S.
Abstract: In order to meet the increasingly stringent regulations in terms of pollutant emissions adopted by ICAO-CAEP in last years, a redesign of aero-engine combustors has been required and, today, lean combustion technology can be considered as the most effective solution. In this context, common design tools and standard RANS predictive techniques are often not capable of properly characterizing combustors performances. Thus, computational techniques have been rapidly evolving towards an extensive use of Large-Eddy Simulation (LES) or hybrid RANS methods. This paper presents the numerical analysis of an experimental partially premixed flame fed by a dilute spray of acetone[1], exploiting a two-phase Eulerian-Lagrangian approach combined with the Flamelet Generated Manifold (FGM) combustion model in the context of LES techniques. All simulations have been performed with thecode Ansys Fluent 15.0. A comparison both in non-reactive and reactive conditions of the obtained results with experimental data and conventional RANS solution has been realized in order to highlight the LES capabilities to give a new insight into the physics of reactive two-phase flows, particularly on the unsteady evolution of turbulent spray flames involving particles dispersion, evaporation and combustion.